New Normal Mindset in Human Resources Strategies of Entrepreneurs for Sustainability in Thailand - et. al., Dr.Tosaporn Mahamud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This articleIt aims to study Business organization Need to prepare a response And keep up with the changes Environment and situation The purpose of the content is to be described. One Strategic Human Resources Management for Dealing with All Situations and Context of NNM second HRS, NNM - Approach to New Context of Entrepreneurs for Generating Consistent Roles third Strategies of Entrepreneur for NNM Business Sustainable four Identity Representing Sustainability when Challenging with COVID-19 Crisis in Thailand five Issues that should be emphasized by entrepreneurs And the issues that entrepreneurs should pay attention to Both in the HRS strategic human resource division, creating a sustainability concept for the benefit of business organizations and entrepreneurs.